TiO2-WO3 Composite Nanotubes by Alloy Anodization: Growth and Enhanced Electrochromic Properties - Nah, Yoon-Chae; Ghicov, Andrei; Kim, Dam-Hee; Berger, Stefan; Schmuki, Patrik (Journal of the American Chemical Society, 2008)
The present work demonstrates that uniform and highly ordered arrays of TiO_2-WO_3 nanotubes can be grown by anodization of Ti alloys in an ethylene glycol/fluoride based electrolyte under selected electrochemical conditions. These aligned mixed oxide nanotube structures are highly suitable for enhanced electrochromic reactions; in particular we show that already small amounts of WO_3 (such as 0.2 at%) present in the tube oxide drastically improve the electrochromic properties (contrast, onset potential, cycling stability) of nanotube layer based devices.
EAM Import::2019-03-13